2009
DOI: 10.1590/s0034-70942009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the FiO2 Delivered by Seven Models of the Self-Inflating Bag-Mask System

Abstract: All resuscitators capable of being connected to an O2 reservoir delivered a higher O2 concentration when connected to this device. Resuscitators that do not have this capability delivered a higher O2 concentration than the ones that could be connected to this device but are used without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…( 5 , 12 , 13 ) Although those studies investigated important characteristics, such as the oxygen fraction delivered by MRs with and without an oxygen reservoir, the present study evaluated other equally important properties that had not yet been reported in the national literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 5 , 12 , 13 ) Although those studies investigated important characteristics, such as the oxygen fraction delivered by MRs with and without an oxygen reservoir, the present study evaluated other equally important properties that had not yet been reported in the national literature.…”
Section: Discussionmentioning
confidence: 99%
“…( 5 , 12 , 13 ) Embora esses estudos tenham investigado características importantes, como, por exemplo, a fração de oxigênio ofertada pelos RMs com e sem o reservatório de oxigênio, o presente estudo avaliou outras propriedades igualmente importantes que ainda não haviam sido relatadas na literatura nacional.…”
Section: Discussionunclassified
“…There are clinical situations in which professionals must personalize the amount of oxygen and, consequently, the percentage of oxygen mixed with atmospheric air offered to each patient. Some BVMs have been tested using oxygen flows of 1, 5, 10 and 15 litres per minute (L/min) with and without an oxygen reservoir, and this oxygen flow influences the fraction of inspired oxygen (FiO2) offered to the patient [7]. It is therefore important to know how an oxygen reservoir can influence the FiO2 offered by the BVM device.…”
Section: Oxygen Flowmentioning
confidence: 99%
“…Oxygen Flow The use of an oxygen source connected to the AIR and the location of oxygen entering the balloon can influence the positive expiratory pressure (PEP) and TV generated regardless of the BVM brand [ 7 ]. In adults, resuscitators must be able to function properly with high oxygen flows, as during an emergency the flow meter can be changed and the resuscitator must remain in optimal condition.…”
Section: Technical Reportmentioning
confidence: 99%
“…Godoy et al (52) também determinou que o fluxo de O 2 influencia a FiO 2 ofertada por sete RMs. Os RMs foram testados utilizando fluxos de O 2 de 1, 5, 10 e 15L/min com e sem reservatório de O 2 .…”
Section: Fluxo De Oxigênio Fornecido Ao Rmunclassified